2022
DOI: 10.3390/nu14193937
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights in the Physiopathology and Management of Obesity-Related Kidney Disease

Abstract: Obesity is recognized as an independent risk factor for the development of kidney disease, which has led to the designation of obesity-related glomerulopathy (ORG). Common renal features observed in this condition include glomerular hypertrophy, glomerulosclerosis, haemodynamic changes and glomerular filtration barrier defects. Additionally, and although less studied, obesity-related kidney disease also involves alterations in renal tubules, including tubule hypertrophy, lipid deposition and tubulointerstitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 90 publications
0
9
0
2
Order By: Relevance
“…In the future, we will explore the roles of mTORC1 in adipose fibrosis caused by ageing and other factors that are still unclear. In addition, the ectopic adipose deposition caused by obesity causes fibrosis of the liver, kidney [ 31 , 32 ], and other organs. In this study, we mainly discuss the role of mTORC1 in the fibrosis of adipose tissue itself.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we will explore the roles of mTORC1 in adipose fibrosis caused by ageing and other factors that are still unclear. In addition, the ectopic adipose deposition caused by obesity causes fibrosis of the liver, kidney [ 31 , 32 ], and other organs. In this study, we mainly discuss the role of mTORC1 in the fibrosis of adipose tissue itself.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, several observational studies have analyzed kidney outcomes in patients with or without CKD who undergo BS [ 9 , 34 , 35 , 36 ]. Overall, results have consistently shown that BS is associated with slower eGFR decline [ 8 , 9 , 37 , 38 , 39 ]. In line with these findings, patients in our cohort experienced an improvement in eGFR in the short and medium term.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies point to a connection between lipotoxicity and CKD. Moreover, adipose tissue depots directly related to the kidney (renal sinus fat) might also play a role [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that megalin could be a therapeutic target for obesity-related CKD. In obesity-related renal disease, numerous factors contribute to the development and progression of CKD, including insulin resistance, lipotoxicity, dysregulation of adipocytokine secretion, contribution of different fat depots, etc., ( Sandino et al, 2022 ). Endocytosis impairment in tubule may partially contribute to CKD progression.…”
Section: Obesity-related Renal Diseasementioning
confidence: 99%